Endogenous Hours and the Wealth of Entrepreneurs - Felix Wellschmied; Emircan Yurdagul (Institute of Labor Economics (IZA), 2019)
US entrepreneurs typically work long hours in their firms and these hours form a large part of the firms' labor input. This paper studies the role of endogenous owner hours in shaping the wealth distribution among entrepreneurs. We introduce owners' endogenous labor supply into a model of entrepreneurial choice and financial frictions. The model fits well the levels and the dispersion of wealth among entrepreneurs. Long owner hours incentivize poor, highly productive individuals to be owners and help the most productive owners to accumulate large quantities of wealth. On net, owners working long hours decreases the median owner wealth and increase wealth dispersion among owners. Differently, the ability to work sufficiently short hours incentivizes owners to run low productivity firms with high wealth to income ratios. Finally, alternative calibrations ignoring the endogenous labor supply of owners lead to owners that are much richer than in the data and overstate the effect of financial frictions in the economy.
Keywords: E23; J22; J23; L26; 330; entrepreneurship; wealth accumulation; labor supply; firm dynamics